2009
DOI: 10.1089/jwh.2008.0982
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in Risk of Cervical Intraepithelial Lesions

Abstract: Background: This study examines the relationship among psychosocial factors, behavioral risks for abnormal cervical cytology, and abnormal cervical cytology. Methods: A self-administered questionnaire was used to measure perceived stress, discrimination, lifetime stressful events, optimism, social support, and psychological state. Women with normal Pap smears attending a primary care clinic and women attending a colposcopy clinic because of an abnormal Pap smear were eligible. The scores between the two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Unhealthy life style, negatively rated life events, lack of social support, coping style, and distress, often associated with smoking, alcohol abuse, and illegal drugs addition, have been reported as risk factors for cervical cancer [ 45 47 ], especially among low-educated women [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy life style, negatively rated life events, lack of social support, coping style, and distress, often associated with smoking, alcohol abuse, and illegal drugs addition, have been reported as risk factors for cervical cancer [ 45 47 ], especially among low-educated women [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the suppressive effects of chronic stress and increased GC levels on CMI, and given the importance of cell-mediated immune responses in HR-HPV clearance, chronic psychological stress may participate in promoting HR-HPV persistence and thus HPV-associated cervical cancer progression mediated by cortisol. Indeed, several studies have demonstrated associations between psychosocial stress and prevalence and progression of HPV-associated cervical dysplasia and cancer [ 25 31 ], although not unequivocally so [ 32 , 33 ]. Among the hitherto published studies, however, most used cross sectional or retrospective designs and focused on the association between stress and cervical dysplasia or cancer; only two studies were of prospective nature [ 31 , 32 ] and only one directly focused on the association between chronic stress (i.e., bereavement) and HR-HPV infection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are some observed (biochemical) changes in plasma protein levels, as confirmed by studies of their values during illness and stress. There are various study results on animals and humans which support the association between psychological stress, infections and carcinogenesis (Table 1 and Table 2) [25,48,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Animal model studies show that stress increases values of acute phase proteins [71].…”
Section: Discussionmentioning
confidence: 99%